Coupling and Coordination Between Water Poverty and High-quality Economic Development in Yellow River Basin - Wang Shuhe; Wang Lijun (Shuitu baochi tongbao)
[Objective] The coupling and coordination between water poverty and high-quality economic development was analyzed in order to provide a reference for the efficient use of water resources and high-quality economic development in the Yellow River basin. [Methods] Based on data from nine provinces in the Yellow River basin from 2010 to 2019, The entropy weight method was used with data from nine provinces (or regions) in the Yellow River basin from 2010 to 2019 to determine the water poverty index weight. The coupling coordination degree model and gray correlation degree were used to analyze the coupling coordination degree and mutual influence between water poverty and high-quality economic development in the Yellow River basin. [Results] ① The water poverty index of the provinces in the Yellow River basin generally increased over time, and the level of high-quality economic development was generally low, with obvious regional differences. ② The degree of coupling coordination showed a fluctuating upward trend, with a general spatial distribution pattern of “high in the east and low in the west”. ③ The gray correlation coefficients between the indicators of the two systems of water poverty and high-quality economic development were both greater than 0.5, which was in a relatively high level of correlation. [Conclusion] The level of water poverty and the level of high-quality economic development in the Yellow River basin have generally improved over time, and the level of coupling coordination is generally low. Most provinces are in a state of mild imbalance.